Standarization of Experiential Learning Facilitator in West Sumatera - Endang Sepdanius; Anton Komaini; Rini Afriani (Jurnal Cakrawala Pendidikan, 2018)
Abstract: The purpose of this research was to standardize experiential learning (EL) facilitators in outdoor activities in West Sumatera. The result of this research is expected that the EL facilitator is competent with the issuance of professional certificate by the National Agency for Profession Certification (BNSP). This research uses quantitative method with analytic descriptive approachand has been done in two stages. First, Implementation of workshop program for experiential learning facilitators and produce recommendations for workshop participants. Second, conductied a competency test of EL facilitators by the National Agency for Profession Certification (BNSP). The number of respondents was 20 facilitators from 4 providers (n=20). Data were collected using Indonesian national competence standard of tourism sector in the field of outbound / experiential learning facilitator and BNSP test. The data were processed using descriptive statistical analysis technique.  The results of the study showed that 19 participants were declared competent and 1 incompetent participant. The results of the study showed that 19 participants were declared competent and 1 participants declared incompetent by the National Agency for Profession Certification (BNSP). These results indicate that the EL workshop program resulted 19 participants have been declared competent in guiding outdoor activities using experiential learning approach.Keyword: facilitator of experiential learning, standardization, outbound training Standarisasi Pada Fasilitator Experiential Learning di Sumatera Barat Abstrak: Tujuan penelitian ini adalah melakukan standarisasi pada fasilitator experiential learning (EL) dalam kegiatan outdoor di Sumatera Barat. Hasil penelitian diharapkan dapat memberikan masukan untuk dikeluarkannya sertifikat profesi oleh Badan Nasional Sertifikat Profesi (BNSP) kepada fasilitator EL karena memenuhi syarat kompetensi. Penelitian ini menggunakan metode kuantitatif dengan pendekatan deskriptif analitik dilakukan dalam dua tahap: (1) melaksanaan program workshop bagi fasilitator EL dan memberikan rekomendasi pada peserta, (2) melakukan uji kompetensi fasilitator EL oleh BNSP. Jumlah responden adalah 20 orang fasilitator dari 4 provider (n=20). Data dikumpulkan menggunakan standar kompetensi kerja nasional Indonesia sektor pariwisata bidang kepemanduan outbound/fasilitator experiential learning dan pelaksanaan test profesi oleh BNSP. Data diolah menggunakan teknik analisis statistik deskriptif. Hasil dari penelitian menunjukan bahwa 19 fasilitator dinyatakan lulus dan 1 orang dinyatakan tidak lulus oleh BNSP. Hasil ini menunjukan bahwa program workshop EL menghasilkan 19 peserta yang kompeten dalam memandu kegiatan outdoor menggunakan pendekatan experiential learning. Kata Kunci: fasilitator experiential learning, standarisasi, outbound training